Profile of the Spleen Transcriptome in Beef Steers with Variation in Gain and Feed Intake - Lindholm-Perry, Amanda K.; Kern, Rebecca J.; Keel, Brittney N.; Snelling, Warren M.; Kuehn, Larry A.; Freetly, Harvey C. (Frontiers in Genetics, 2016)
We have previously identified components of the immune system contributing to feed intake and gain in both the rumen and small intestine of beef steers. In this study, we examined the spleen, a major lymphatic organ near the digestive tract, to determine whether it was also influencing individual feed efficiency status through immune responses. Animals (n=16) that were divergent for gain and intake were selected for tissue sampling. The spleen transcriptomes were evaluated by microarray. A total of 1,216 genes were identified as differentially expressed. Genes were over-represented in Kyoto encyclopedia of genes and genomes (KEGG) pathways including biological regulation, protein folding, cell communication, immune systems process, response to stress and RNA metabolic process. Several stress response or heat shock genes including HSPH1, HSPA1A, HSPA4, DNAJB4, DNAJA4, etc., were identified as a stress response functional gene cluster in the low gain-low intake animals. These genes were up-regulated amongst the low gain-low intake animals compared to all other groups. Canonical pathways associated with the differentially expressed genes included the coagulation system, extrinsic prothrombin activation, protein ubiquitination, unfolded protein response and aldosterone signaling in epithelial cells. An analysis of expressed copy number variable (CNV) genes in the spleen produced some of the same genes and gene families that were differentially expressed. Our data suggests the splenic contribution to some of the underlying variation among gain and intake within this group of animals may be a result of immune function and stress response. In addition, some of the differences in immune response functions may be related to gene copy number.